How can I transform −λ△t= (N(t+△t)−N(t)) / (△t) into the formula dN/dt=−λN using limits? This is in relation to radioactive decay for those that are wondering, thank you for your help and time...

How can I transform −λ△t= (N(t+△t)−N(t)) / (△t) into the formula dN/dt=−λN using limits? This is in relation to radioactive decay for those that are wondering, thank you for your help and time...

Calculus: Proofs

Show that the rectangle of a minimum perimeter for a given area A is always a square.

prove that 1/infinity is equal to zero using definition of a derivative

1/n+1/(n+1)+...1/2n>0.63 Prove that in two ways.

The Lagrange form of the Error Bound states that the n+1 term of a Taylor Approximation gives you the remainder such that F(x)=Pn(x)+Rn(x), but what does that mean? I understand that the goal...

Let h and g have relative maxima at x0.

When finding delta, use the absolute value of x-2 is less than 2 so that delta=min{2,__} This is what I've done so far: f(x)=1/x L=1/2 a=2 Find...

Using derivatives a = dv/dt, v = ds/dt and |v| = speed, show that if an object is moving on a straight line, then its speed is increasing when its velocity v and its acceleration a have the same sign...

Using derivatives a = dv/dt, v = ds/dt and |v| = speed, show that if an object is moving on a straight line, then its speed is increasing when its velocity v and its acceleration a have the same sign...

A cone is made of a circular plate of a given radius R by cutting a sector of some angle Q and welding the remaining edges. Draw the graph of the volume V of the resulting cone as a function of Q...

I am trying to figure out how to do this proof using the quotient remainder theorem

If f(x)=Σx4n/(4n)! ....prove that the 4th derivative equals f (x)

Hi, buddies. Please me in my task to answer this questions. As far as my questions, I'm just looking for "What are the real world application of limits (calculus limits) for Industrial Engineering...

1) given the double angle identity for cosine: cos2θ=cos2θ-sin2θ Prove: cos3θ = cos3θ - 3cosθsin2θ and: cos4θ = cos4θ - 6cos2θsin2θ + sin2θ 2)...